Civil Engineering - Theory of Structures - Discussion
Discussion Forum : Theory of Structures - Section 1 (Q.No. 14)
14.
Keeping the depth d constant, the width of a cantilever of length l of uniform strength loaded with a uniformly distributed load w varies from zero at the free end and
Discussion:
23 comments Page 1 of 3.
ALEX said:
5 months ago
M/I = F/Y.
WL2/2 = F * Z = F * BD2/6.
B = 3WL2/(F*D2).
WL2/2 = F * Z = F * BD2/6.
B = 3WL2/(F*D2).
(1)
Vishal Singh said:
2 years ago
If it is zero at the free end then it should be a uniformly varying load with zero at the free end.
How can uniformly distributed load is zero at free?
How can uniformly distributed load is zero at free?
Abiy said:
2 years ago
The right Answer is A.
(1)
Abiy said:
2 years ago
@Gupta.
Thanks for your explanation but for load w uniformly distributed from free end zero.
W=wl/2.
Which it's Mmax=wl/3 At the fixed end.
So, the answer is C.
Thanks for your explanation but for load w uniformly distributed from free end zero.
W=wl/2.
Which it's Mmax=wl/3 At the fixed end.
So, the answer is C.
(1)
Jeganathan said:
3 years ago
Sigma is nothing but f (bending stress).
And Z(section modulus) = bd2/6.
Then,
B.M. at fixed support is wl2/2.
M= f.(I/Y)
M=f.Z
wl2/2 = f * Z.
wl2/2 = f * bd2/6.
b= (3wl2)/fd2.
Answer C.
And Z(section modulus) = bd2/6.
Then,
B.M. at fixed support is wl2/2.
M= f.(I/Y)
M=f.Z
wl2/2 = f * Z.
wl2/2 = f * bd2/6.
b= (3wl2)/fd2.
Answer C.
(5)
Bishwo said:
4 years ago
Bending moment at fixed =1/3 (wl^2) /2.
1/3 is because it's a triangular slab of thickness d and with b. 1 part of whole rectangle will give BM at the fixed end.
1/3 is because it's a triangular slab of thickness d and with b. 1 part of whole rectangle will give BM at the fixed end.
(1)
Michael said:
4 years ago
Thanks @Anshul Gupta.
SHUBHAM SIDDHARTH NAYAK said:
4 years ago
Cantilever carrying UDL- BM at fixed end = wl^2 /2.
We know, M = fz.
Wl^2/2= f *(bd^2/6),
b =3wl^2/fd^2.
We know, M = fz.
Wl^2/2= f *(bd^2/6),
b =3wl^2/fd^2.
Syed Mazhar said:
5 years ago
@Dhananjay.
From bending eq
M/I= f/y=E/R
M=(I/y)f
M=zf.
From bending eq
M/I= f/y=E/R
M=(I/y)f
M=zf.
Dhananjay said:
6 years ago
@Anshul,
How can you equate BM with S*Z? Here, units are different. Please explain.
How can you equate BM with S*Z? Here, units are different. Please explain.
Post your comments here:
Quick links
Quantitative Aptitude
Verbal (English)
Reasoning
Programming
Interview
Placement Papers